PENERAPAN PUZZLE PETA UNTUK MENINGKATKAN KEMAMPUAN SPATIAL THINKING DAN CRITICAL THINKING - Hilmy, Anggit Athoillah; Kurniawati, Aida; Murtini, Sri; Prasetya, Sukma Perdana (Jurnal Pendidikan : Riset dan Konseptual, 2025)
This study aims to apply the Map Puzzle learning method in order to improve students' spatial thinking and critical thinking skills. The method used in this research is an experimental method with a research design involving two groups, namely the experimental group and the control group. The experimental group will receive treatment in the form of applying map puzzle learning media in geography learning, while the control group will follow conventional learning without using media. The research subjects were students of SMP Cendikia class 9A with 30 students and 9B with 30 students. The instrument used to measure students' spatial thinking and critical thinking skills consists of 30 multiple choice questions. This test will be given before (pretest) and after (posttest) applying map puzzle media. The results showed that the application of the Map Puzzle method can significantly improve the spatial thinking and critical thinking skills of students. Learners are more actively involved in the learning process, and the use of map puzzles provides variations in learning methods that can motivate learners to think more critically and understand spatial concepts better. Map Puzzle learning media is effectively used as a learning strategy in developing spatial and critical thinking skills.